The Paradoxes of Time Travel: (trans. Marcin Iwanicki, Joanna Klara Teske) - Lewis, David; Iwanicki, Marcin; Teske, Joanna Klara (Roczniki Filozoficzne, 2023)
The original: ”The Paradoxes of Time Travel”. American Philosophical Quarterly 13 (1976): 145–152. Translation with the Publisher's permission. This paper argues that time travel is possible, and that the paradoxes of time travel are oddities, not impossibilities. The defense of the possibility of time travel involves a commitment to (a) enduring things having temporal as well as spatial parts, (b) psychological continuity and connectedness and causal continuity as criteria of personal identity, and (c) a distinction between external and personal time.